Republic of Armenia : Request for Three-Year Arrangement Under the Extended Fund Facility and Extended Credit Facility, and Cancellation of the Stand-By Arrangement; Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for the Republic of Armenia. (IMF Staff Country Reports; Country Report ;, 2010)
Economic activity appears to be recovering, underpinned by a strong policy response. Fiscal consolidation will be crucial to maintain debt sustainability and support the envisaged external adjustment over the medium term. Sound monetary and exchange rate policies are essential to maintain macroeconomic stability. Improvements in tax administration are needed to achieve the program's goals of sound public finances and stronger economic growth. Broader efforts to strengthen the business environment are crucial to boost medium-term growth prospects. Risks to the program are manageable.